2003
DOI: 10.1016/s0168-8227(02)00177-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired β-cell function and insulin sensitivity in Japanese subjects with normal glucose tolerance

Abstract: The development of type 2 diabetes mellitus is characterized by both impaired beta-cell function and increasing insulin resistance. To clarify the roles of them in developing type 2 diabetes, we evaluated insulin resistance by HOMA-IR and insulin secretion by HOMA beta-cell in 453 Japanese subjects whose fasting plasma glucose (FPG) and HbA(1c) levels were within normal range. HOMA beta-cell was found to decrease in the over 30 years groups, while HOMA-IR increased with body mass index (BMI). To analyze the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 34 publications
3
61
1
2
Order By: Relevance
“…Quatro artigos (8%) tratam de abordagens relativas à definição de valores de referência para o índice HOMA; o mais recente envolve 6.511 americanos (1,13,46,75) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Quatro artigos (8%) tratam de abordagens relativas à definição de valores de referência para o índice HOMA; o mais recente envolve 6.511 americanos (1,13,46,75) .…”
Section: Resultsunclassified
“…Tais técnicas vêm servindo ao entendimento dos mecanismos regulatórios envolvidos na homeostase da glicose e na patogênese do diabetes tipo 2 (46,56,86) , à avaliação de risco e predição do desenvolvimento de diabetes tipo 2 (DM2) em estudos epidemiológicos (23,26) , para avaliação do curso clinicoterapêutico do diabetes (39,76,82) , para medida da RI associada à síndrome dos ovários policísticos (3,4,83,84) ; bem como para a determinação da RI e da BcC, base para trabalhos acerca da patogenia genético-molecular da RI e dos distúrbios da tolerância à glicose (7,34) .…”
Section: Introductionunclassified
“…HOMA ISI values calculated by using OGTT data show the insulin sensitivity of tissues (9). Differences among HOMA ISI values of the groups show that insulin sensitivity of tissues is decreased in the fi rst degree relatives (p<0.005 F; 11.38 One Way -ANOVA) (Tab.…”
Section: Discussionmentioning
confidence: 94%
“…Criteria for the diagnosis of diabetes, impaired fasting glucose, and impaired glucose tolerance (IGT) were made according to ADA criteria (7). HOMA IR , HOMA ISI , AUC Glucose values were also calculated with data obtained from the OGTT results (8,9,10 …”
Section: Designmentioning
confidence: 99%
“…6 Kadowaki, et al reported that early insulin response was an independent predictor for diabetes. 7 In Japanese men with normal glucose tolerance, even a small increase in BMI produced a decrease in beta cell function disproportionate to that in insulin sensitivity, 8 indicating that there are inherent differences between Asian and Caucasian populations. Furthermore, Asia …”
Section: Introductionmentioning
confidence: 99%